Effect of iron supplementation on iron stores and total body iron after whole blood donation. Issue 8 (27th May 2016) - Cable, Ritchard G.; Brambilla, Donald; Glynn, Simone A.; Kleinman, Steven; Mast, Alan E.; Spencer, Bryan R.; Stone, Mars; Kiss, Joseph E.; ,
Abstract : BACKGROUND: Understanding the effect of blood donation and iron supplementation on iron balance will inform strategies to manage donor iron status. STUDY DESIGN AND METHODS: A total of 215 donors were randomized to receive ferrous gluconate daily (37.5 mg iron) or no iron for 24 weeks after blood donation. Iron stores were assessed using ferritin and soluble transferrin receptor. Hemoglobin (Hb) iron was calculated from total body Hb. Total body iron (TBI) was estimated by summing iron stores and Hb iron. RESULTS: At 24 weeks, TBI in donors taking iron increased by 281.0 mg (95% confidence interval [CI], 223.4‐338.6 mg) compared to before donation, while TBI in donors not on iron decreased by 74.1 mg (95% CI, −112.3 to −35.9; p < 0.0001, iron vs. no iron). TBI increased rapidly after blood donation with iron supplementation, especially in iron‐depleted donors. Supplementation increased TBI compared to controls during the first 8 weeks after donation: 367.8 mg (95% CI, 293.5‐442.1) versus −24.1 mg (95% CI, −82.5 to 34.3) for donors with a baseline ferritin level of not more than 26 ng/mL and 167.8 mg (95% CI, 116.5‐219.2) versus −68.1 mg (95% CI, −136.7 to 0.5) for donors with a baseline ferritin level of more than 26 ng/mL. A total of 88% of the benefit of iron supplementation occurred during the first 8 weeks after blood donation. CONCLUSION: Donors on iron supplementation replaced donated iron while donors not on iron did not. Eight weeks of iron supplementation provided nearly all of the measured improvement in TBI. Daily iron supplementation after blood donation allows blood donors to recover the iron loss from blood donation and prevents sustained iron deficiency.